Assessment of the relationships between deleterious oral habits that may cause orthodontic anomalies and psychological and socio-demographic factors - Cenk Doruk; Zeynep Çoban Büyükbayraktar (Cumhuriyet University, 2017)
Objectives: The aim of this study is to identify the relation between the deleterious oral habits (DOH) which can cause orthodontic anomalies such as finger sucking, nail biting, lip chewing, bruxism and psychological and socio-demographic factors. Materials and Methods: 64 males, 71 females, between the ages of 9 and 12, including their parents have been included into our study. In our study, a survey form consisting of Clinic Examination Data Form, Socio-demographic Data Form, Children's Depression Inventory (CDI), Child State Trait Anxiety Inventory (CSTAI) has been applied to patients. Results: DOH have been observed on 62,5 % of the male children and % 52,1 of the female children, but these results are not statistically significant (p>0,05). No statistically significant associations were found between DOH and CDI (p>0,05). No statistically significant associations were found between the CSTAI status section score and trait section score and DOH (p>0,05). Statistically significant associations were found between family type and DOH (p<0,05). Conclusions: While there were no significant associations between anxiety and depression and DOH, there were a significant associations family type from socio-demographic factors and DOH.